Comportamento adaptativo de Lutzomyia longipalpis (Diptera: Psychodidae) às áreas urbanas da cidade de Teresina-PI. - Martins, Kelsilândia Aguiar (2011)
The sand fly Lutzomyia longipalpis (Diptera: Psychodidae) is currently appointed as the main vector of visceral leishmaniasis in the Americas. The growth of cities in areas originally endemics to American Visceral Leishmaniasis (AVL) resulted in the spread of the disease at the same time that observed the adaptation of this species to the urban environment.Changes in behavior of L.longipalpis that enabled the adapt to increasing losings of biodiversity, as well as the frequent exposure of the vector to insecticides evident in urban areas, could justify the increasing population of the species and consequently the spread of disease for these environments .Thus, we selected sixty houses spread among three areas with increasing stages of occupation of an area endemic for AVL in Teresina-PI. We evaluated the correlation between the density of L.longipalpis captured and different aspects, such as population density of animals, vegetation cover and socio-economic aspects in each house. In addition to the correlations, the feeding preference of the vector between the predominant plant species in the neighborhoods, as well as the presence of metabolic mechanisms of resistance among the captured insects were tested. The results showed that over the growing occupations, represented by three areas, L.longipalpis demonstrate its adaptive nature through an apparent opportunistic behavior in relation to sources of carbohydrates and blood. On the evolutionary point of view, this behavior may have favored its vector competence in urban areas among the limited presence of food sources, as well as in various environments encountered.